PENERAPAN OUTBOUND TRAINING UNTUK PENINGKATAN KOHESIVITAS TIM DI UPT PPK BKD PROVINSI SULAWESI SELATAN - Muis, Ismarli; Suci, Faradilla Nurul; Sahnur, Akhdan Asirih Afif Siddiq; Oddang, Andi Nabila Fitriyyah; Nurjaya, Ima Tri (Devote: Jurnal Pengabdian Masyarakat Global, 2023)
Outbound training is an experiental learning process that is carried out to improve interpersonal relationships, team cohesiveness, and behavior modification by providing changes in individual characteristics. Outbound Training aims to help 13 employees of the Technical Implementation Unit (UPT) Potential and Competency Assessment (PPK) of the Regional Personnel Agency (BKD) of South Sulawesi Province. The method in this study is to use the One Group Pre-Post Design Method, this method is supported by giving a team cohesiveness questionnaire as a pre-test then a post-test after giving intervention in the form of outbound training. Based on the results of the paired sample t-test, the 2-tailed significance value is 0.002 <0.05, which means that there is a significant difference between the pre-test and post-test, so it can be concluded that there is an effect of the outbound training process on increasing team cohesiveness at UPT PPK BKD South Sulawesi Province, this can be seen in the results of data analysis, namely that there are differences in group cohesiveness values before and after the implementation of outbound training for employees of 13 UPT PPK BKD South Sulawesi Province. It can be concluded that Outbound training is effective in increasing team cohesiveness.